Venoarterial Extracorporeal Membrane Oxygenation for Severe Neonatal Acute Respiratory Distress Syndrome in a Developing Country - Xiaoyang Hong; Zhe Zhao; Zhe Zhao; Zhenqiu Liu; Change Liu; Jie Wang; Xueli Quan; Hui Wu; Qiong Ji; Jianwei Sun; Donglinag Cheng; Zhichun Feng; et al. (Frontiers Media S.A., 2020)
Objective: Extracorporeal membrane oxygenation (ECMO) has supported oxygen delivery and carbon dioxide removal in neonatal severe respiratory failure for more than 4 decades. The definition and diagnosis of neonatal acute respiratory distress syndrome (ARDS) was made according to the criteria first established by a Montreux Conference in 2017. By far, there has been no ECMO efficiency studies in neonatal ARDS. We aimed to compare the outcomes of neonates with severe ARDS supported with and without ECMO.Design: Retrospective pair-matched study.Setting: In the present retrospective pair-matched study, the outcomes of severe ARDS with ECMO support and without ECMO support were analyzed and compared. Propensity score matching was conducted. The study subjects were selected from a China Neonatal ECMO (CNECMO) study. In total, five hospitals were included in the CNECMO study. The patients were matched with demographic and clinical data. The primary endpoint was in-hospital mortality. Secondary outcomes included ventilator-time, ICU stay, hospitalization costs and cranial MRI results.Patients: 145 neonates with severe ARDS (Oxygenation Index, OI ≥16) from 5 hospitals.Interventions: No interventions.Measurements and Main Results: We collected the data of 145 neonates with severe ARDS (Oxygenation Index, OI≥16) from 5 hospitals. Among them, 42 neonates received venoarterial (VA) ECMO support, and the remaining 103 neonates were treated with conventional mechanical ventilation. The mortality of ECMO-supported neonates was not significantly different compared with the ESLO neonatal respiratory-supported from 2012 to 2018 (23.8 vs. 32.5%, p = 0.230). After matching with the propensity score we got 31 pairs. The ECMO-supported neonates had a lower in-hospital mortality (6 of 31, 19.4%) vs. non ECMO-supported patients (18 of 31, 58.1%) (p = 0.002). Hospitalization costs of survivors in ECMO-supported neonates were significantly higher than that of non-ECMO-supported neonates (p < 0.001). There was no difference of ventilator-times (p = 0.206), ICU stay (p = 0.879) and cranial MRI (p = 0.899) between the survivors of ECMO-supported and non-ECMO-supported neonates with ARDS.Conclusions: By far, there has been no ECMO efficiency studies in neonatal ARDS. This study found that ECMO-support have superior outcomes compared with non-ECMO-support in neonates with severe ARDS.